Improvement of Organizational Citizenship Behavior (OCB) through Strengthening Transformational Leadership, Job Satisfaction, and Self-Efficacy - Rosandi, Ari; Hardhienata, Soewarto; Sunaryo, Widodo; Zainal Arifin, M. (Opción, 2019)
Organizational Citizenship Behavior (OCB) is believed to be able to improve the efficiency and effectiveness of organizations such as schools because it contains a component of a teacher’s loyalty and dedication with compliance with organizational policies and policies as well as responsibilities for assignments and jobs even outside of the job description. The correlational statistical approach is used in the study followed by the SITOREM method to set recom-mendations and find the order of priority scale for improvement of indicators of each variable. The study was conducted on PNS teachers in the “A” accredited State Junior High School in Depok with a study population of 372 teach- ers, with a proportional random sample of 193 teachers. Based on the results of research sequentially shows that there is a positive relationship between independent variables and OCB variables as follows: 1) transformational leadership (ry1 = 0.711,α < 0.05); 2) job satisfaction (ry2 = 0.792, α < 0.05); and 3) self-efficacy (ry3 = 0.829, α < 0.05); 4) there is a positive and significant relationship between the principal’s transformational leadership and job sat- isfaction together with OCB with the correlation coefficient ry12 = 0.813 (α < 0.01); 5) there is a positive and significant relationship between the principal’s transformational leadership and self-efficacy together with OCB with the cor- relation coefficient ry13 = 0, 848 (α < 0.01); 6) there is a positive and significant relationship between job satisfaction and self-efficacy together with OCB with the correlation coefficient ry23 = 0.844 (α < 0.01); and 7) there is a positive and significant relationship between transformational leadership, job satisfaction, and self-efficacy together with OCB with the correlation co- efficient ry123 = 0.854 (α < 0.01). The results of the SITOREM analysis show the indicators that need to be corrected priority are: 1). Magnitude, 2). Strength, 3). Generality, 4). Supervision, 5). Coworkers, 6). Income, 7). The work itself, 8). Sense of Justice, 9). Promotion, 10). Intellectual Stim- ulation, 11). Idealized Influence, 12). Individual Consideration, 13). Conscientiousness, 14). Altruism, 15). Courtesy, and 16) Civic Virtue, while the sequence is maintained by Inspirational Motivation and Sportmanship.